Detection of chromosomal bla(CTX-M-2) in diverse Escherichia coli isolates from healthy broiler chickens - Ferreira, J. C.; Penha Filho, Rafael A. Casarin [UNESP]; Andrade, L. N.; Berchieri Junior, Angelo [UNESP]; Darini, A. L. C. (Wiley-Blackwell, 2014)
The rise of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli in food-producing animals is a growing concern for public health. We investigated ESBL producers isolated from broiler chickens in Brazil and characterized 19 CTX-M-2-producing E.coli. The ISCR1 was detected upstream of the chromosome-located gene bla(CTX-M-2), associated with sul-1 type integron structure. CTX-M-2-producing E.coli exhibited different PFGE-types and phylogenetic groups, showing a non-clonal dissemination. The sequence types found (ST93, ST155 and ST2309) have been associated with humans and animals worldwide. Herein, we report the chromosomal location of bla(CTX-M-2) on E.coli, highlighting the risks of multidrug-resistant bacteria in food-producing animals.
Keywords: Brazil; extended-spectrum beta-lactamase; food- producing animals; poultry; qnr